2012
DOI: 10.1073/pnas.1205431109
|View full text |Cite
|
Sign up to set email alerts
|

Soybean susceptibility to manufactured nanomaterials with evidence for food quality and soil fertility interruption

Abstract: Based on previously published hydroponic plant, planktonic bacterial, and soil microbial community research, manufactured nanomaterial (MNM) environmental buildup could profoundly alter soil-based food crop quality and yield. However, thus far, no single study has at once examined the full implications, as no studies have involved growing plants to full maturity in MNM-contaminated field soil. We have done so for soybean, a major global commodity crop, using farm soil amended with two high-production metal oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
419
8
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 467 publications
(477 citation statements)
references
References 45 publications
33
419
8
2
Order By: Relevance
“…However, the inhibition of bacterial nitrogen fixation did not necessarily result in nitrogen shortage for the plants; soybeans exposed to high doses of nanoceria actually grew better those exposed to low doses of nanoceria in the Priester study, 83 suggesting that the plants successfully used an alternative source of nitrogen for growth. In a related study, Bandyopadhyaya et al 84 observed that nanoceria at 31-125 mg/l significantly inhibited the growth of Sinorhizobium meliloti, the primary symbiotic nitrogen fixing bacteria of alfalfa.…”
Section: Soil Exposures In Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the inhibition of bacterial nitrogen fixation did not necessarily result in nitrogen shortage for the plants; soybeans exposed to high doses of nanoceria actually grew better those exposed to low doses of nanoceria in the Priester study, 83 suggesting that the plants successfully used an alternative source of nitrogen for growth. In a related study, Bandyopadhyaya et al 84 observed that nanoceria at 31-125 mg/l significantly inhibited the growth of Sinorhizobium meliloti, the primary symbiotic nitrogen fixing bacteria of alfalfa.…”
Section: Soil Exposures In Plantsmentioning
confidence: 99%
“…The authors also observed nanoceria in the vasculature of leaf veins, providing further evidence that nanoceria may be transported from roots to shoots with water through vascular tissues. 82 Priester et al 83 noted that soybean exposed to 100-1000 mg/kg nanoceria had root ceria content of up to 200 mg/kg but that translocation was minimal. Plant growth and yield were modestly reduced but importantly, nitrogen fixation was almost entirely eliminated.…”
Section: Soil Exposures In Plantsmentioning
confidence: 99%
“…In Glycine max (soybean), nitrogen fixation potential per nodule was also severely diminished at medium and high nano CeO 2 treatments (50, 100 g/kg soil), which are correlated to absent bacteroids in nodules (Priester et al, 2012). Similarly, nano TiO 2 disrupted Rhizobium-legume symbiosis between Pisum sativum (peas) and R. leguminosarum bv.…”
Section: Impact On Agronomic and Yield Characteristicsmentioning
confidence: 99%
“…To date, the knowledge of ENMs-crop interactions in soil-based systems is very limited. In some published trials, sand or soil was either amended with nanomaterial powders or with ENMs suspensions (Du et al, 2011;Dimkpa et al, 2012;El-Temsah and Joner, 2012;Priester et al, 2012;Zhao et al, 2012a;Khodakovskaya et al, 2013). A design with outdoor lysimeters under field condition was first introduced to investigate the impact of ENMs on Triticum aestivum (wheat) growth and soil enzyme activities; here, the topsoil was ex-situ amended with TiO 2 and ZnO nanoparticles (Du et al, 2011).…”
Section: Laboratory Designed Exposure Conditionsmentioning
confidence: 99%
“…However, this could release an excess of ENMs in soil, ground water, and food products, with unknown consequences (Klaine et al, 2008;Boxall and Molhave, 2011). ENPs like ZnO and CeO 2 ENPs, widely used in food and commercial products, are potentially toxic to humans and plants (Nel et al, 2006;Lin et al, 2009;Moos et al, 2011;Lee et al, 2012;Mihranyan et al, 2012;Priester et al, 2012). These, as well as silver (Ag), gold (Au), and iron oxide (Fe 3 O 4 ) ENPs, are potentially toxic to soil microbiota (Barrena et al, 2009;Ge et al, 2011;Sinha et al, 2011;Bandyopadhyay et al, 2012a).…”
mentioning
confidence: 99%